Architectural Mind in Transition - Ana Paula Rainha; Ana Bordalo (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Background: the research developed in the field of Architecture Education, considering the preceding texts about an Architectonic Mind. Purpose: to “draw” a turning point, based on the previous research, so that, through those results, we can give an answer to the new challenges. Methodology: based on a critical analysis, to revisit concepts, in a changing world context, towards the discovery of new methodologies, reflecting in the present and future concerns and expectations.  Results and conclusions: the idea is to "close" a “step”, through the review and conclusion of the earlier investigations and formulate the construction of a new path, where new premises emerge, so that we can prepare the future architects, aware of the condition of the real world now, but conscious, however, of the pillars on which the today demanded transformations are based on.